High agreement on family affluence between children's and parents' reports: international study of 11-year-old children. Issue 12 (15th April 2008) - Andersen, A; Krølner, R; Currie, C; Dallago, L; Due, P; Richter, M; Örkényi, Á; Holstein, B E
Abstract : Objective: To examine the agreement between parents' and children's reports on four items of family affluence: number of cars, own bedroom, number of family holidays and number of computers, and to analyse predictors of disagreement. Design: Cross-sectional child–parent validation study of selected items from an internationally standardised questionnaire. Setting: Survey conducted in schools in Denmark, Germany, Hungary, Italy, Poland and Scotland. Participants: 972 11-year-old children and their parents responded to the questionnaires. Results: The child item response rates were high (above 93%). The per cent agreement was low for holidays spent with family (52.5%), but high for the other three items of family affluence (76.2–88.1%). The kappa coefficients were good or excellent for all items (between 0.41 and 0.74) and the gamma coefficients were strong for all items (between 0.56 and 0.96). Children from single-parent families were more likely to over-report family affluence (OR 2.67; CI 1.83 to 3.89). Conclusions: Young adolescents' self-reports of family affluence are fairly valid across the six countries. This finding suggests that the variables measured can be used in epidemiological studies that aim at ranking children according to socioeconomic position.